Tahlil al-Asas al-Mafahimiy li Kitab “Al-Arabiyyah al-Muyassarah li Fahmi al-Qur’an wa al-Sunnah” wa al-Tathbiq alaih fi Madrasah Sunan Ampel al-Mutawassithah wa Madrasah Darul Qur’an al-Mutawassithah / Analysis of the Conceptual Basis of the Book “Al-Arabiyyah al-Muyassarah li Fahmi al-Qur’an wa al-Sunnah” and Its Implementation at Sunan Ampel Junior High Schools and Darul Qur’an Junior High Schools - Isro'atul Choliliyah; Ibnu Samsul Huda; Moch. Wahib Dariyadi; Heba Tawfiqie Abu Eyadah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2026)
Teaching Arabic at the SMP level faces various practical challenges, including its status as a local subject, the diverse backgrounds of students, and limited instructional time. This study analyzes the conceptual framework of the book Al-ʿArabiyyah al-Muyassarah li Fahm al-Qurʾān wa al-Sunnah by Prof. Dr. Nurul Murtadho (2025) and describes its implementation in SMP, specifically SMP Sunan Ampel Mojokerto and SMP Darul Quran Singosari. A descriptive qualitative approach was used, with data collected through interviews, classroom observations, and a study of teaching documents (RPP); with research participants consisting of 22 eighth-grade students at SMP Sunan Ampel, who already possess Arabic reading and writing skills and come from a public school background; and 22 seventh-nineth grade students at SMP Darul Quran Junior, who come from an Islamic boarding school background. The textbook consists of six lessons with periodic review units and is based on the Lexical Approach, repetitive exercises, teacher modeling, pair conversations, integrated teaching of the four skills, limited graded morphology, and the use of flashcards to support oral practice. Its implementation in two junior high schools with different institutional contexts yielded positive responses from both teachers and students. This study concludes that the textbook is pedagogically coherent, aligned with the characteristics of junior high school students as beginner learners of Arabic, and effective as a teaching resource for the local-content Arabic course in SMP.يواجه تدريس اللغة العربية في المرحلة المتوسطة العديد من التحديات العملية، بما في ذلك وضعها كمادة محلية، وتنوع خلفيات الطلاب، ومحدودية الوقت المخصص للتدريس. تحلل هذه الدراسة الإطار المفاهيمي لكتاب العربية الميسرة لفهم القرآن والسنة لنور المرتضى (2025)، وتصف تطبيقه في المدارس المتوسطة (SMP)، وتحديدا في مدرسة سونان أمبيل المتوسطة بماجاكرطا ومدرسة دار القرآن المتوسطة بسنجاساري. وقد استخدم نهج وصفي نوعي، حيث تم جمع البيانات من خلال المقابلات والملاحظات الصفية ودراسة وثائق التدريس (RPP)؛ وشمل المشاركون في البحث 22 طالبا من الصف الثامن في مدرسة سونان أمبيل المتوسطة، الذين يمتلكون بالفعل مهارات القراءة والكتابة باللغة العربية وينتمون إلى مدارس عامة؛ و22 طالبا من الصفوف من السابع إلى التاسع في مدرسة دار القرآن المتوسطة، الذين ينتمون إلى مدارس معهدية. يتألف الكتاب من ستة دروس مع وحدات مراجعة دورية، ويستند إلى النهج المعجمي، والتمارين المتكررة، والنمذجة من قبل المعلم، والمحادثات الثنائية، والتدريس المتكامل للمهارات الأربع، وعلم الصرف المتدرج المحدود، واستخدام البطاقات الومضية لدعم الممارسة الكلام. وقد أسفر تطبيقه في مدرستين إعداديتين ذات سياقات مؤسسية مختلفة عن ردود فعل إيجابية من كل من المعلمين والطلاب. تخلص هذه الدراسة إلى أن الكتاب المدرسي يتسم بالاتساق التربوي، ويتوافق مع خصائص طلاب المرحلة المتوسطة باعتبارهم متعلمين مبتدئين للغة العربية، كما أنه فعال كمورد تعليمي لمقرر اللغة العربية ذي المحتوى المحلي في المرحلة المتوسطة.